Severe acute mountain sickness and suspected high altitude cerebral edema related to nitroglycerin use - Mazzuero, G.; Mazzuero, A.; Pascariello, A. (High Altitude Medicine & Biology, 2008)
An elite mountaineer reported severe acute mountain sickness and ataxia during an 8000-m expedition and concomitant use of transdermal nitroglycerin patches aimed to prevent frostbites. Use of nitroglycerin for this purpose is off-label, and its safety has not been assessed. Moreover, a relation between nitrate-induced cerebral vasodilation and high altitude cerebral edema is theoretically possible on a pathophysiological basis. It is our opinion that nitroglycerin use at high altitude should be discouraged, as efficacy in the prevention of frostbites is questionable and safety has not been assessed.